Saving behavior of non-financial firms in Turkey - Hamza Demircan; Sumru Öz (Koç University-TÜSİAD Economic Research Forum (ERF), 2018)
This paper proposes a method to calculate undistributed profits, thus saving rates of non-financial firms using only the information given in their balance sheets. This allows us to analyze the saving behavior of non-financial firms even in the absence of their statement of cash flows, which contains "dividend payments" data. The balance sheets of non-financial firms are provided by TurkStat only for 2013 and 2014, so this paper is confined to the cross sectional analysis of the saving behavior of non-financial firms in Turkey. We find that the saving rate increases as past net profit margin increases for firms with profits in the preceding year. For the firms which declare loss in the preceding year, saving rate increases as the past value of net profit margin decreases. Our findings for the rest of the firm-level determinants are consistent with the previous studies: Firm size plays a role on corporate savings; leverage ratio has a negative impact on the saving rate; and the positive impact of export orientation is higher for SMEs.
Keywords: D22; E21; E22; C21; O16; 330; Firm Behavior; Savings of non-financial firms; Turkey